Effects of high-frequency, high-intensity transcutaneous electrical nerve stimulation versus intravenous opioids for pain relief after hysteroscopy: a randomized controlled study - Birgitta Platon; Sven-Egron Thörn; Clas Mannheimer; Paulin Andréll (Korean Society of Obstetrics and Gynecology, 2020)
Objective To compare the time spent in the Post-Anesthesia Care Unit (PACU) and the pain-relieving effects of treatment with high-frequency, high-intensity transcutaneous electrical nerve stimulation (TENS) or intravenous (IV) opioids after hysteroscopy. Methods All patients who postoperatively reported a visual analogue scale (VAS) pain score of ≥3 were included in the study. TENS treatment was given with a stimulus intensity between 40 and 60 mA for 1 minute and repeated once if there was insufficient pain relief. In the opioid group, a fractionated dose of 5 mg morphine was administered. If the patient reported insufficient pain relief after the assigned treatment, the patient was reassigned to the other treatment group. Results Seventy-four women were randomized to TENS (n=38) or IV opioids (n=36) for treatment. Both groups reported significant pain relief after discharge from the PACU, with a decrease of VAS scores from 5.6 to 1.4 in the TENS group (P<0.001) and 5.1 to 1.3 in the opioid group (P<0.001). There were no significant differences between the groups. When only the responders in both groups, i.e., patients with VAS scores of <3 on respectively assigned treatments, were compared, the TENS responders (n=22) were found to have spent a significantly shorter time in the PACU (91 vs. 69 minutes, P=0.013) compared to the opioid responders (n=20). Conclusion Using TENS as first line of pain relief may reduce the need for postoperative opioids. In addition, TENS appears preferable as the first line of treatment due to its association with a shorter time spent in the PACU if the patient responds to the treatment. Trial Registration Västra Götalandsregionen Identifier: 211261